USING ROTATING TRIO EXCHANGE (RTE) METHOD IN TEACHING SPEAKING ON ANALYTICAL EXPOSITION TEXT - Mike Amelia (Universitas Mahaputra Muhammad Yamin, 2019)
This research purposed is to find out the effect of using Rotating Trio Exchange (RTE) Method in teaching Speaking on Analytical Exposition Text at Universitas Singaperbangsa Karawang (UNSIKA). This research used experimental class. The sample of this research was 30 students ( 1A) at experimental class and 30 students in control class(1B). The instrument of this reasearch was speaking test. The research finding of this research indicated that the Rotating Trio Exchange method gave positive effect on students’ speaking ability from pre-test to post-test. Students’ ability in speaking analytical exposition text analyzed by using t-test statistical which t calculated = 5,74 and t table (0,95:69) = 1,67. It could be concluded that t calculated > t table. So, the null hypothesis (H0) was rejected while alternative hypothesis (H1) was accepted.